Where the sky begins : a novel - Bowen, Rhys (Lake Union Publishing, 2022)
"London, 1940. Bombs fall and Josie Banks's world crumbles around her. Her overbearing husband, Stan, is unreachable, called to service. Her home, a ruin of rubble and ash. Josie's beloved tearoom boss has been killed, and Josie herself is injured, with nothing left and nowhere to go. Evacuated to the English countryside, Josie ends up at the estate of the aristocratic Miss Harcourt, a reluctant host to the survivors of the Blitz. Awed as she is by the magnificent landscape, Josie sees opportunity. Josie convinces Miss Harcourt to let her open a humble tea shop, seeing it as a chance for everyone to begin again. When Josie meets Mike Johnson, a handsome Canadian pilot stationed at a neighboring bomber base, a growing intimacy brings her an inner peace she's never felt before. Then Stan returns from the war. Now a threat looms larger than anyone imagined. And a dangerous secret is about to upend Josie's life again. Her newfound courage will be put to the test if she is to emerge, like a survivor, triumphant"--Dust jacket flap.